(untitled) (Italian Review of Legal History, 2021)
The essay examines the different types of bonds present in the documentation of Central-Northern Italy in the framework of regulation written in the notarial formularies of Ranieri di Perugia, Salatiele and Zaccaria Martino, where these acts follow the traditional documents like sales, donations and wills. Credit deeds are written in a similar way since the same standards are present everywhere with a sort of common plot. In most Italian towns, notaries usually write credit documents on vacchette, which contain the main information relating to the contract, directly in front of the interested parties. Then they transcribe the same acts in registers in which the extended version of the documents is proposed. The writing of the rough copy generally includes all guarantee clauses in a concise way; subsequent registration in the notarial protocols is authenticated by the notaries and guaranteed by the public authority. The use of notebooks of minuta is simultaneous with the increase of credit agreements and in their organization in the notarial formularies.